THE EFFECT OF ECONOMIC GROWTH, UNEMPLOYMENT RATE AND HUMAN DEVELOPMENT ON POVERTY IN INDONESIA (Panel Model Approach in 4 Poorest Provinces) - Ananto Wibowo; M. Rismawan Ridha (Sam Ratulangi University, 2021)
The implementation of various policies in poverty alleviation in Indonesia has yielded good results. This condition is reflected by the downward trend in the percentage of poor people who reached a single digit in 2018. However, this has not much-changed the conditions in some of the poorest provinces such as Maluku, East Nusa Tenggara, West Papua, and Papua. This study aims to analyze the effect of Economic Growth, Unemployment Rate, and Human Development Index (HDI) on poverty in the four poorest provinces from 2011 to 2018. The research data sources from Statistics Indonesia (BPS) with the analytical tool used in estimating the panel data regression model is the Fixed Effect Model (FEM). The results show that economic growth and HDI have a negative effect on the poverty. In reverse, the Unemployment Rate has an insignificant effect. Based on the research results, the government advised coordinating with relevant stakeholders in formulating policies to increase welfare and purchasing power, improve the quality of education, and optimize health services in the four poorest provinces.Â